2019
DOI: 10.4103/ijri.ijri_16_19
|View full text |Cite
|
Sign up to set email alerts
|

Bilio-cutaneous fistula obliteration with NBCA

Abstract: Biliary fistula and bile leakage are complications that can occur during hepato-biliary surgery (both open and laparoscopic) and percutaneous biliary intervention. In some cases, spontaneous resolution is documented but more often re-intervention (surgical or percutaneous) is necessary. We present the case of a male patient who underwent right hepatectomy with bilio-digestive anastomosis for a cholangiocarcinoma which developed a bilo-cutaneous fistula through the path of a previously inserted percutaneous tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…While most of the cases were due to ruptured hepatic abscesses following tumor ablation, one patient had developed a biliary fistula after pancreatitis. 1 Bottari et al 4 and Alberto et al 5 performed successful obliteration of a BCF using glue. Furthermore, Ierardi et al demonstrated successful treatment of a BCF following the removal of a PTBD catheter using an Amplatzer vascular plug.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the cases were due to ruptured hepatic abscesses following tumor ablation, one patient had developed a biliary fistula after pancreatitis. 1 Bottari et al 4 and Alberto et al 5 performed successful obliteration of a BCF using glue. Furthermore, Ierardi et al demonstrated successful treatment of a BCF following the removal of a PTBD catheter using an Amplatzer vascular plug.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we injected NBCA glue to fill the fistula cavity, followed by placing micro-coils to occlude the leaking bile duct. In literature review, 4 cases of biliocutaneous fistulas successfully sealed by interventional radiologic management have been reported [ 4 , 8 , 9 ]. The causes of such fistulas formation include Whipple operation for pancreatic tumor, hepatic surgery for hydatid disease, and prolonged percutaneous biliary drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The use of retrievable covered stents is gaining a foothold in the last years, accordingly to numerous studies, with a high rate of clinical success, providing an effective and definitive treatment [ 55 ]. On the other hand, other options which may be taken in consideration are the employment of balloon occlusions [ 46 ] or embolizing materials, such as fibrin, coils, and acetic acid, with an increased use of the N-butyl cyanoacrylate, according to the literature [ 56 , 57 , 58 ].…”
Section: Percutaneous Transhepatic Biliary Drainagementioning
confidence: 99%